Macroeconomic Challenges with EU Accession in Southeastern Europe : An Overview - Sorsa, Piritta (Washington, D.C. : International Monetary Fund, 2006)
The paper reviews key macroeconomic challenges with EU accession in Southeastern Europe (SEE). Most of the countries in the region are years away from EU accession and need substantial progress to meet the key macroeconomic criteria-the establishment of a functioning market economy and macroeconomic stability. The former calls for further structural reforms. While macroeconomic stability is essential throughout the EU accession process, the importance of specific outcomes increases in the last stage of accession, when countries face decisions to apply for entry into the ERM2 and the Maastricht criteria (Bulgaria and Romania). The main challenges with establishing macroeconomic stability in other countries are related to sustainability of their monetary frameworks, risks from rapid financial deepening, and further fiscal consolidation to support growth and stabilization. Most of the SEE countries have room to lower public spending and increase the share of pro-growth spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet